An asymmetric fission island driven by shell effects in light fragments - P. Morfouace; J. Taieb; A. Chatillon; L. Audouin; G. Blanchon; R. N. Bernard; N. Dubray; N. Pillet; D. Regnier; H. Alvarez-Pol; F. Amjad; P. André; et al. (Nature, 2025)
Abstract Nuclear fission leads to the splitting of a nucleus into two fragments 1,2 . Studying the distribution of the masses and charges of the fragments is essential for establishing the fission mechanisms and refining the theoretical models 3,4 . It has value for our understanding of r-process nucleosynthesis 5,6 , in which the fission of nuclei with extreme neutron-to-proton ratios is pivotal for determining astrophysical abundances and understanding the origin of the elements 7 and for energy applications 8,9 . Although the asymmetric distribution of fragments is well understood for actinides (elements in the periodic table with atomic numbers from 89 to 103) based on shell effects 10 , symmetric fission governs the scission process for lighter elements. However, unexpected asymmetric splits have been observed in neutron-deficient exotic nuclei 11 , prompting extensive further investigations. Here we present measurements of the charge distributions of fission fragments for 100 exotic fissioning systems, 75 of which have never been measured, and establish a connection between the neutron-deficient sub-lead region and the well-understood actinide region. These new data comprehensively map the asymmetric fission island and provide clear evidence for the role played by the deformed Z = 36 proton shell of the light fragment in the fission of sub-lead nuclei. Our dataset will help constrain the fission models used to estimate the fission properties of nuclei with extreme neutron-to-proton ratios for which experimental data are unavailable.